Automobile shock absorber piston precision machining process

CN122999985APending Publication Date: 2026-10-30ANHUI DINGYUAN METAL PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610642052.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]针对现有汽车减震器活塞加工工艺存在的尺寸精度低、表面质量差、批次一致性不足、加工效率与零件性能难以兼顾等技术问题,本发明提供一种汽车减震器活塞精密加工工艺,通过优化各加工工序的工艺参数,完善质量管控体系,实现活塞的精密加工,提升活塞的尺寸精度、表面质量和结构性能,同时提高加工效率、降低加工成本,满足中高端汽车减震器的使用要求

Benefits of technology

1、本发明通过优化原材料筛选与预处理工艺,选用配比合理的铁铜合金粉末,确保粉末粒度均匀、含水率达标,为后续成型和烧结奠定良好基础,粉末混合过程中精准控制混合比例和转速,使润滑剂均匀分散,提升粉末成型性能,减少生坯缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999985A_ABST
    Figure CN122999985A_ABST
Patent Text Reader

Abstract

The application discloses a kind of automobile shock absorber piston precision machining processes, belong to automobile parts processing technical field, the process sequentially includes raw material screening and pretreatment, powder mixing and forming, sintering treatment, precision shaping, numerical control finishing, surface strengthening treatment, precision detection and finished product packaging.The application controls the process parameter of each working procedure accurately, especially optimizes sintering temperature, shaping pressure and finishing cutting parameter, in combination with on-line detection and whole-process quality control, so that the size tolerance of the piston is controlled within ±0.01mm, the surface roughness is as low as Ra0.04μm, while the density, hardness and wear resistance of the piston are improved, ensuring the structural stability and service life of the piston under high-frequency reciprocating motion and high-temperature environment;The process is reasonable, operable, and the material utilization rate is as high as 95% or more, suitable for large-scale batch production, can meet the stringent requirements of high-end automobile shock absorber on piston precision and reliability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of automotive parts processing technology, specifically relating to a precision machining process for automotive shock absorber pistons. It is applicable to the large-scale precision production of various automotive shock absorber pistons, and is especially suitable for the processing of shock absorber pistons for mid-to-high-end passenger vehicles with high requirements for dimensional accuracy and performance. Background Technology

[0002] The shock absorber is a core component of the vehicle suspension system. Its function is to suppress spring rebound and absorb road impacts. As a key moving part inside the shock absorber, the piston's machining accuracy, surface quality, and structural performance directly determine the damping characteristics, sealing performance, and service life of the shock absorber. The machining process of automotive shock absorber pistons is mainly divided into two categories: forging and powder metallurgy. Among them, powder metallurgy involves mixing metal powders, pressing them into shape, and then sintering them. It has advantages such as simple process, low cost, high material utilization rate, and suitability for mass production, and has become the mainstream process for piston machining.

[0003] However, existing powder metallurgy processing technology still has many shortcomings: 1. Uneven powder mixing leads to uneven density of the sintered blank, resulting in weak points and internal cracks, affecting the strength and durability of the piston; 2. Unreasonable control of sintering process parameters leads to large piston dimensional deformation, making it difficult to meet the precision tolerance requirement of ±0.01mm; 3. Insufficient optimization of cutting parameters during finishing process makes it difficult to achieve the required surface roughness, and the machining accuracy of key structures such as damping holes is low, affecting the damping characteristics of the shock absorber; 4. Imperfect surface treatment process results in insufficient wear resistance and corrosion resistance of the piston surface, making it prone to wear and rust under high-frequency reciprocating motion and complex working conditions, shortening the service life of the shock absorber; 5. Incomplete quality control system leads to poor batch-to-batch consistency, with some unqualified products entering the market, affecting product reliability.

[0004] Therefore, developing a precision machining process for automotive shock absorber pistons that is reasonable, precise, efficient, low-cost, and can effectively improve piston performance has become a pressing technical problem to be solved in this field. Summary of the Invention

[0005] To address the technical problems of low dimensional accuracy, poor surface quality, insufficient batch consistency, and difficulty in balancing processing efficiency and part performance in existing automotive shock absorber piston processing technology, this invention provides a precision machining process for automotive shock absorber pistons. By optimizing the process parameters of each processing step and improving the quality control system, precision machining of the piston is achieved, improving the dimensional accuracy, surface quality, and structural performance of the piston, while simultaneously increasing processing efficiency and reducing processing costs, thus meeting the usage requirements of mid-to-high-end automotive shock absorbers.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A precision machining process for automotive shock absorber pistons includes the following steps: Step A: Raw Material Screening and Pretreatment: Iron-copper alloy powder is selected as the core raw material, with an iron powder content of 85-90 wt% and a copper powder content of 10-15 wt%. This ratio of iron-copper alloy powder ensures both the strength and wear resistance of the piston, while also improving the powder's molding and sintering properties. The powder is screened to a particle size of 100-150 mesh using vibration screening to remove impurities and large particles, ensuring uniform particle size. The screened powder is then sent to a drying oven for drying at 80-100℃ for 1-2 hours. After drying, the powder moisture content is controlled to ≤0.1% to avoid moisture affecting the powder's mixing uniformity and molding quality.

[0007] Preferably, the iron-copper alloy powder has a uniform microstructure, a flowability of 15-20s / 50g, and a loose packing density of 3.5-4.2g / cm³, which further improves the molding effect and sintering consistency.

[0008] Step B, Powder Mixing and Molding: The pretreated iron-copper alloy powder and lubricant are mixed at a mass ratio of 98-99:1-2. The mixture is fed into a high-speed mixer and mixed at a speed of 200-300 r / min for 30-60 min to ensure that the lubricant is evenly dispersed in the metal powder, thereby improving the powder's flowability and formability. The uniformly mixed powder is then fed into a special mold and cold-pressed under a pressure of 200-300 MPa for 5-10 s to produce a piston green blank with the same shape as the finished piston. The density of the green blank is controlled at 6.5-6.8 g / cm³ to ensure a dense structure and avoid excessive deformation during subsequent sintering.

[0009] Preferably, the lubricant is zinc stearate with a purity of ≥99% and a particle size of 200-250 mesh, which has good lubrication effect and can be completely decomposed in the subsequent sintering process, without leaving any impurities that would affect the piston performance.

[0010] Step C, Sintering Treatment: The piston green blank is fed into a vacuum sintering furnace, employing a segmented heating sintering process. This process effectively removes lubricant from the green blank, preventing bubbles and cracks during sintering, while ensuring uniform density and strength of the sintered blank. The specific steps are as follows: First, the temperature is increased to 400-500℃ at a rate of 5-10℃ / min and held for 30-40 minutes to allow the lubricant to fully decompose and volatilize, preventing lubricant residue from causing porosity in the blank; then, the temperature is increased to 1080-1120℃ at a rate of 3-5℃ / min, which is the optimal sintering temperature for the iron-copper alloy powder, and held for 60-90 minutes to allow the powder particles to melt before complete melting, forming a dense bond through atomic diffusion. The sintering atmosphere is a mixture of hydrogen and nitrogen. The mixed gas contains 10-15% hydrogen and 85-90% nitrogen. Hydrogen acts as a reducing agent to prevent oxidation of the green body, while nitrogen maintains stable pressure inside the furnace and improves sintering uniformity. After sintering, the green body is cooled in stages at a rate of 2-3℃ / min until it reaches room temperature. This avoids excessively rapid cooling that could cause thermal stress and deformation in the green body, resulting in a sintered green body with a density of 7.0-7.2 g / cm³ and an ultimate tensile strength of 300-430 MPa, meeting the strength requirements of the piston.

[0011] Preferably, the temperature and atmosphere concentration are monitored in real time during the sintering process, the temperature fluctuation does not exceed ±5℃, and the protective atmosphere in the furnace is controlled at 0.001-0.01MPa.

[0012] Step D, Precision Shaping: Since the sintered billet may undergo slight deformation during the sintering process, affecting the accuracy of subsequent finishing, precision shaping is necessary. The sintered billet is fed into a precision shaping machine, employing a cold shaping process with a shaping pressure of 150-200 MPa and a holding time of 3-5 seconds. This process shapes key areas such as the outer circle, end faces, and steps of the billet, correcting dimensional deviations generated during sintering and ensuring that the critical dimensional tolerances of the billet are controlled within ±0.01 mm. This lays the foundation for subsequent finishing and further improves the density and structural compactness of the billet.

[0013] Step E, CNC finishing: The shaped blank is finished using a five-axis CNC machining center. The five-axis CNC machining center has the advantages of high positioning accuracy and strong machining flexibility, and can realize high-precision machining of complex piston structures. During the machining process, key structures such as the piston bore, damping bore, and annular groove are processed sequentially. The cutting parameters are optimized as follows: cutting speed of 160-280 m / min, feed rate of 0.1-0.2 mm / r, and depth of cut of 0.05-0.1 mm. These parameters effectively reduce cutting deformation and prevent scratches and burrs on the piston surface. The damping bore is machined using a combination of drilling and reaming. The basic hole is drilled first, and then reamed for finishing, ensuring that the hole diameter tolerance is controlled within ±0.01 mm and the hole position deviation does not exceed 0.01 mm. This ensures the uniform distribution of the damping bore and thus ensures the stability of the damping characteristics of the shock absorber. After machining, the piston surface is finely ground to further reduce the surface roughness, controlling it to Ra0.04-0.08 μm, thereby improving the fit accuracy and sealing performance between the piston and the cylinder.

[0014] Preferably, a diamond tool with a tip radius of 0.1-0.2 mm is selected. Diamond tools have high hardness and good wear resistance, which can effectively improve machining accuracy and surface quality and extend tool life. During the machining process, emulsion cooling is used, and the cooling temperature is controlled at 20-25℃ to prevent tool overheating and wear and thermal deformation of the piston machining surface.

[0015] Step F, Surface Strengthening Treatment: To improve the wear resistance, corrosion resistance, and surface hardness of the piston, the precision-machined piston is subjected to steam treatment. The piston is placed in a steam treatment furnace at a temperature of 180-220℃ for 20-30 minutes, forming a protective oxide layer with a thickness of 5-15μm on the piston surface. This oxide layer is tightly bonded to the piston substrate, effectively isolating it from external corrosive media. At the same time, it increases the surface hardness of the piston to 180-250HV, reduces the coefficient of friction to 0.15-0.25, reduces frictional loss during the reciprocating motion of the piston in the cylinder, and extends the service life of the piston and shock absorber.

[0016] Step G, Precision Inspection: Establish a comprehensive quality inspection system, employing a combination of fully automated optical inspection equipment and magnetic induction detection to comprehensively inspect the piston's dimensional accuracy, surface quality, hardness, and density, ensuring product quality compliance. Dimensional inspection covers key indicators such as outer diameter, piston bore diameter, damping hole position, and annular groove width, with an inspection accuracy of ±0.001mm, conforming to precision tolerance standards. The minimum tolerance after dimensional adjustment is controlled within ±0.01mm. Surface quality inspection uses high-definition visual inspection to detect surface defects such as scratches, dents, and oxide layer defects. Hardness testing uses a Vickers hardness tester, randomly selecting samples for testing to ensure surface hardness meets requirements. Density testing uses the water displacement method to test the density of the sintered blank and finished piston, ensuring uniform density. Products that fail inspection are reworked; those that still fail after rework are scrapped, ensuring a pass rate of ≥99.5% and improving batch-to-batch product consistency.

[0017] Preferably, the inspection adopts a precision tolerance standard, the minimum tolerance after dimensional adjustment is controlled within ±0.01mm, and the inspection pass rate is ≥99.5%.

[0018] Step H, Finished Product Packaging: The qualified pistons are placed in an ultrasonic cleaner and cleaned with a neutral cleaning agent for 10-15 minutes to remove cutting fluid, oil, and impurities from the piston surface. After cleaning, they are placed in a drying oven and dried at 60-80℃ for 30-40 minutes to ensure the piston surface is dry and free of moisture. After drying, they are individually wrapped in rust-proof paper to prevent rusting. The packaged pistons are then placed in shockproof boxes, clearly labeled with the product model, specifications, and production date, before being stored for future transport and storage.

[0019] Preferably, ultrasonic cleaning is used, the cleaning solution is a neutral cleaning agent, the cleaning time is 10-15 minutes, and the piston surface is free of oil and impurities after cleaning.

[0020] Compared with the prior art, the beneficial effects of this invention are as follows: 1. This invention optimizes the raw material screening and pretreatment process, selects iron-copper alloy powder with reasonable proportions, ensures uniform powder particle size and meets the moisture content standard, laying a good foundation for subsequent molding and sintering. During the powder mixing process, the mixing ratio and rotation speed are precisely controlled to ensure uniform dispersion of lubricant, improve powder molding performance, and reduce green defects.

[0021] 2. A segmented heating and sintering process is adopted to precisely control the heating rate, sintering temperature, holding time, and sintering atmosphere. This effectively removes lubricant and avoids bubbles, cracks, and oxidation defects in the sintered green body. At the same time, it improves the density and strength of the green body, with a density of 7.0-7.2 g / cm³ and an ultimate tensile strength of 300-430 MPa, ensuring that the piston has good structural stability and load-bearing capacity.

[0022] 3. A precision forming process is added to correct dimensional deviations during sintering and provide a high-precision blank for finishing. The finishing process uses a five-axis CNC machining center and diamond tools, optimizes cutting parameters, and combines drilling and reaming to control the key dimensions of the piston within ±0.01mm and the surface roughness as low as Ra0.04μm. This improves the fit and sealing performance between the piston and the cylinder and ensures the stability of the damper's damping characteristics.

[0023] 4. Surface strengthening is achieved through steam treatment, forming a protective oxide layer on the piston surface. This significantly improves the piston's wear resistance, corrosion resistance, and surface hardness, reduces the coefficient of friction, extends the service life of the piston and shock absorber, and meets the requirements of high-frequency reciprocating motion and high-temperature environments.

[0024] 5. Establish a comprehensive precision testing system that combines fully automated optical testing and magnetic induction testing to achieve comprehensive testing of piston dimensions, surface quality, hardness, and density. This ensures that the product quality is qualified, the consistency between batches is good, and the pass rate is ≥99.5%, preventing unqualified products from entering the market and meeting the stringent requirements of mid-to-high-end automotive shock absorbers for piston precision and reliability. Attached Figure Description

[0025] Figure 1 This is a flowchart illustrating the precision machining process for automotive shock absorber pistons proposed in this invention. Figure 2 This is a schematic diagram of the structure of an automotive shock absorber piston according to a precision machining process proposed in this invention.

[0026] In the figure: 1 Piston body, 2 Piston hole, 3 Damping hole, 4 Annular groove, 5 Oxide layer. Detailed Implementation

[0027] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Example

[0028] Refer to the instruction manual appendix Figure 1-2 A precision machining process for automotive shock absorber pistons includes the following steps: Step A, Raw Material Screening and Pretreatment: Iron-copper alloy powder is selected as the core raw material, with an iron powder content of 85wt% and a copper powder content of 15wt%. The powder is screened with a particle size of 100 mesh. After removing impurities by vibration screening, it is sent to a drying oven for drying at 80℃ for 2.0h. The moisture content of the powder after drying is controlled at 0.08%. The microstructure of the iron-copper alloy powder is uniform, the flowability is 15s / 50g, and the loose density is 3.5g / cm³. Step B, Powder Mixing and Molding: The pretreated iron-copper alloy powder and zinc stearate lubricant are mixed at a mass ratio of 98:2. The zinc stearate has a purity of 99% and a particle size of 200 mesh. The mixture is fed into a high-speed mixer, with a mixing speed of 200 r / min and a mixing time of 60 min, to obtain a uniform mixed powder. The mixed powder is then fed into a special mold and cold-pressed under a pressure of 200 MPa for 10 s to form a piston green. The green density is controlled at 6.5 g / cm³. Step C, Sintering Treatment: The piston green blank is fed into a vacuum sintering furnace and sintered using a segmented heating method. First, the temperature is increased to 400℃ at a rate of 5℃ / min and held for 40min to remove the lubricant. Then, the temperature is increased to 1080℃ at a rate of 3℃ / min and held for 90min. The sintering atmosphere is a mixture of hydrogen and nitrogen, with hydrogen accounting for 10% and nitrogen accounting for 90%. The protective atmosphere in the sintering furnace is controlled at 0.001MPa, and the temperature fluctuation is controlled within ±5℃. After sintering, the blank is cooled in segments at a rate of 2℃ / min until it reaches room temperature, resulting in a sintered green blank with a density of 7.0g / cm³ and an ultimate tensile strength of 300MPa. Step D, Precision Shaping: The sintered billet is fed into a precision shaping machine and cold shaping is adopted. The shaping pressure is 150MPa and the holding time is 5s. The outer circle, end face and steps of the billet are shaped to correct the dimensional deviations generated during sintering and make the key dimensional tolerance of the billet ±0.01mm. Step E, CNC Finishing: A five-axis CNC machining center is used to finish the shaped blank, sequentially machining the piston hole, damping hole, and annular groove. A diamond tool with a tip radius of 0.1 mm is used, with a cutting speed of 160 m / min, a feed rate of 0.1 mm / r, and a depth of cut of 0.05 mm. The damping hole is machined using a combination of drilling and reaming, with the hole diameter tolerance controlled within ±0.01 mm and the hole position deviation within 0.008 mm. After machining, the piston surface is precision ground to a surface roughness of Ra 0.08 μm. Emulsion cooling is used during machining, with the cooling temperature controlled at 20℃. Step F, Surface strengthening treatment: The finished piston is sent into a steam treatment furnace and treated at 180°C for 30 minutes to form a protective oxide layer with a thickness of 5μm on the piston surface, so that the surface hardness reaches 180HV and the friction coefficient is reduced to 0.25. Step G, Precision Inspection: A combination of fully automated optical inspection equipment and magnetic induction detection was used to comprehensively inspect the piston's dimensional accuracy, surface quality, hardness, and density. Dimensional inspection met precision tolerance standards, with a minimum tolerance of ±0.01mm. After surface quality inspection, no scratches, dents, or other defects were found. Hardness testing was conducted using a Vickers hardness tester, and the hardness test was passed. Density testing was performed using the water displacement method, and the density test met the standards. The pass rate for this inspection was 99.5%. Non-conforming products were reworked. Step H, Finished Product Packaging: The qualified pistons are sent into an ultrasonic cleaner and cleaned with a neutral cleaning agent for 15 minutes to remove surface oil and impurities. After cleaning, they are sent into a drying oven to dry at 60°C for 40 minutes. After drying, they are individually packaged with rust-proof paper, then placed in a shockproof packaging box, labeled, and put into storage. Example

[0029] Refer to the instruction manual appendix Figure 1-2 A precision machining process for automotive shock absorber pistons includes the following steps: Step A, Raw Material Screening and Pretreatment: Iron-copper alloy powder is selected as the core raw material, with an iron content of 88wt% and a copper content of 12wt%. The powder is screened with a particle size of 120 mesh. After removing impurities by vibration screening, it is sent to a drying oven for drying at 90℃ for 1.5h. The moisture content of the powder after drying is controlled at 0.05%. The microstructure of the iron-copper alloy powder is uniform, the flowability is 18s / 50g, and the loose density is 3.8g / cm³. Step B, Powder Mixing and Molding: The pretreated iron-copper alloy powder and zinc stearate lubricant are mixed at a mass ratio of 98.5:1.5. The zinc stearate has a purity of 99.5% and a particle size of 220 mesh. The mixture is fed into a high-speed mixer, with a mixing speed of 250 r / min and a mixing time of 45 min, to obtain a uniform mixed powder. The mixed powder is then fed into a special mold and cold-pressed under a pressure of 250 MPa for 8 s to form a piston green blank with a green blank density of 6.7 g / cm³. Step C, Sintering Treatment: The piston green blank is fed into a vacuum sintering furnace and sintered using a segmented heating method. First, the temperature is raised to 450℃ at a rate of 8℃ / min and held for 35min to remove the lubricant. Then, the temperature is raised to 1100℃ at a rate of 4℃ / min and held for 75min. The sintering atmosphere is a mixture of hydrogen and nitrogen, with hydrogen accounting for 12% and nitrogen accounting for 88%. The protective atmosphere in the sintering furnace is controlled at 0.005MPa, and the temperature fluctuation is controlled within ±4℃. After sintering, the blank is cooled in segments at a rate of 2.5℃ / min until it reaches room temperature, resulting in a sintered green blank with a density of 7.1g / cm³ and an ultimate tensile strength of 360MPa. Step D, Precision Shaping: The sintered billet is fed into a precision shaping machine and cold shaping is adopted. The shaping pressure is 180MPa and the holding time is 4s. The outer circle, end face and steps of the billet are shaped to correct the dimensional deviations generated during sintering and to control the key dimensional tolerance of the billet within ±0.018mm. Step E, CNC Finishing: A five-axis CNC machining center is used to finish the shaped blank, sequentially machining the piston hole, damping hole, and annular groove. A diamond tool with a tip radius of 0.15mm is used, with a cutting speed of 220m / min, a feed rate of 0.15mm / r, and a depth of cut of 0.08mm. The damping hole is machined using a combination of drilling and reaming, with the hole diameter tolerance controlled within ±0.01mm and the hole position deviation within 0.006mm. After machining, the piston surface is precision ground to a surface roughness of Ra0.06μm. Emulsion cooling is used during machining, with the cooling temperature controlled at 22℃. Step F, Surface strengthening treatment: The finished piston is sent into a steam treatment furnace and treated at 200°C for 25 minutes to form a protective oxide layer with a thickness of 10μm on the piston surface, with a surface hardness of 220HV and a friction coefficient of 0.20. Step G, Precision Inspection: A combination of fully automated optical inspection equipment and magnetic induction detection was used to comprehensively inspect the piston's dimensional accuracy, surface quality, hardness, and density. Dimensional inspection met precision tolerance standards, with a minimum tolerance of ±0.01mm. After surface quality inspection, no scratches, dents, or other defects were found. Hardness testing was conducted using a Vickers hardness tester, and the hardness test was passed. Density testing was performed using the water displacement method, and the density test met the standards. The pass rate for this inspection was 99.7%. Non-conforming products were reworked. Step H, Finished Product Packaging: The qualified pistons are sent into an ultrasonic cleaner and cleaned with a neutral cleaning agent for 12 minutes to remove surface oil and impurities. After cleaning, they are sent into a drying oven to dry at 70°C for 35 minutes. After drying, they are individually packaged with rust-proof paper, then placed in a shockproof packaging box, labeled, and put into storage. Example

[0030] Refer to the instruction manual appendix Figure 1-2 A precision machining process for automotive shock absorber pistons includes the following steps: Step A, Raw Material Screening and Pretreatment: Iron-copper alloy powder is selected as the core raw material, with an iron powder content of 90wt% and a copper powder content of 10wt%. The powder is screened with a particle size of 150 mesh. After removing impurities by vibration screening, it is sent to a drying oven for drying at 100℃ for 1.0h. The moisture content of the powder after drying is controlled at 0.03%. The microstructure of the iron-copper alloy powder is uniform, the flowability is 20s / 50g, and the loose density is 4.2g / cm³. Step B, Powder Mixing and Molding: The pretreated iron-copper alloy powder and zinc stearate lubricant are mixed at a mass ratio of 99:1. The zinc stearate has a purity of 99.8% and a particle size of 250 mesh. The mixture is fed into a high-speed mixer, with a mixing speed of 300 r / min and a mixing time of 30 min, to obtain a uniform mixed powder. The mixed powder is then fed into a special mold and cold-pressed under a pressure of 300 MPa for 5 s to form a piston green. The green density is controlled at 6.8 g / cm³. Step C, Sintering Treatment: The piston green blank is fed into a vacuum sintering furnace and sintered using a segmented heating method. First, the temperature is increased to 500℃ at a rate of 10℃ / min and held for 30 min to remove the lubricant. Then, the temperature is increased to 1120℃ at a rate of 5℃ / min and held for 60 min. The sintering atmosphere is a mixture of hydrogen and nitrogen, with hydrogen accounting for 15% and nitrogen accounting for 85%. The protective atmosphere in the sintering furnace is controlled at 0.01 MPa, and the temperature fluctuation is controlled within ±3℃. After sintering, the blank is cooled in segments at a rate of 3℃ / min until it reaches room temperature, resulting in a sintered green blank with a density of 7.2 g / cm³ and an ultimate tensile strength of 430 MPa. Step D, Precision Shaping: The sintered billet is fed into a precision shaping machine and cold shaping is adopted. The shaping pressure is 200MPa and the holding time is 3s. The outer circle, end face and steps of the billet are shaped to correct the dimensional deviations generated during sintering and to control the key dimensional tolerances of the billet within ±0.015mm. Step E, CNC Finishing: A five-axis CNC machining center is used to finish the shaped blank, sequentially machining the piston hole, damping hole, and annular groove. A diamond tool with a tip radius of 0.2 mm is used, with a cutting speed of 280 m / min, a feed rate of 0.2 mm / r, and a depth of cut of 0.1 mm. The damping hole is machined using a combination of drilling and reaming, with the hole diameter tolerance controlled within ±0.01 mm and the hole position deviation within 0.005 mm. After machining, the piston surface is precision ground to a surface roughness of Ra 0.04 μm. Emulsion cooling is used during machining, with the cooling temperature controlled at 25℃. Step F, Surface strengthening treatment: The finished piston is sent into a steam treatment furnace and treated at 220°C for 20 minutes to form a protective oxide layer with a thickness of 15μm on the piston surface, so that the surface hardness reaches 250HV and the friction coefficient is reduced to 0.15. Step G, Precision Inspection: A combination of fully automated optical inspection equipment and magnetic induction detection was used to comprehensively inspect the piston's dimensional accuracy, surface quality, hardness, and density. Dimensional inspection met precision tolerance standards, with a minimum tolerance of ±0.01mm. Surface quality inspection checked for scratches, dents, oxide layer defects, etc., and the surface was free of scratches, dents, and other defects. Hardness testing was conducted using a Vickers hardness tester, and the hardness test was qualified. Density testing was conducted using the water displacement method, and the density test met the standards. The pass rate for this inspection was 99.8%. Unqualified products were reworked. Step H, Finished Product Packaging: The qualified pistons are sent into an ultrasonic cleaner and cleaned with a neutral cleaning agent for 10 minutes to remove surface oil and impurities. After cleaning, they are sent into a drying oven to dry at 80°C for 30 minutes. After drying, they are individually packaged with rust-proof paper, then placed in a shockproof packaging box, labeled, and put into storage.

[0031] The automotive shock absorber pistons processed in the above three embodiments all meet the requirements of dimensional tolerance ±0.01mm, surface roughness Ra0.04-0.08μm, surface hardness 180-250HV, and density 7.0-7.2g / cm³ after testing. After being assembled into automotive shock absorbers, they exhibit stable damping characteristics, excellent wear resistance and corrosion resistance, and a service life that is more than 50% longer than pistons processed by existing processes. The processing efficiency is increased by more than 30%, and the material utilization rate reaches more than 95%, fully meeting the usage requirements of mid-to-high-end automotive shock absorbers.

[0032] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A precision machining process for automotive shock absorber pistons, characterized in that, The steps are as follows: Step A, Raw Material Screening and Pretreatment: Iron-copper alloy powder is selected as the core raw material, with an iron powder content of 85-90wt% and a copper powder content of 10-15wt%. The powder is screened with a particle size of 100-150 mesh to remove impurities and then dried at a temperature of 80-100℃ for 1-2 hours. The moisture content of the dried powder is controlled to be ≤0.1%. Step B, Powder Mixing and Molding: The pretreated iron-copper alloy powder and lubricant are mixed at a mass ratio of 98-99:1-2, the mixing speed is 200-300 r / min, and the mixing time is 30-60 min to obtain a uniform mixed powder; the mixed powder is fed into a special mold and cold-pressed under a pressure of 200-300 MPa for 5-10 s to form a piston green blank, with the green blank density controlled at 6.5-6.8 g / cm³; Step C, Sintering Treatment: The piston green blank is fed into a sintering furnace and sintered using a segmented heating method. First, the temperature is raised to 400-500℃ at a rate of 5-10℃ / min and held for 30-40min to remove the lubricant. Then, the temperature is raised to 1080-1120℃ at a rate of 3-5℃ / min and held for 60-90min. The sintering atmosphere is a mixture of hydrogen and nitrogen, with hydrogen accounting for 10-15% and nitrogen accounting for 85-90%. After sintering, the blank is cooled in segments at a rate of 2-3℃ / min until it reaches room temperature, resulting in a sintered green blank with a density of 7.0-7.2 g / cm³ and an ultimate tensile strength of 300-430 MPa. Step D, Precision Shaping: The sintered billet is fed into a precision shaping machine and cold shaping is adopted. The shaping pressure is 150-200MPa and the holding time is 3-5s. The outer circle, end face and steps of the billet are shaped to correct the dimensional deviations generated during sintering and to control the key dimensional tolerances of the billet within ±0.01mm. Step E, CNC finishing: The shaped blank is finished using a five-axis CNC machining center, sequentially machining the piston hole, damping hole, and annular groove. Diamond tools are used during machining, with a cutting speed of 160-280 m / min, a feed rate of 0.1-0.2 mm / r, and a depth of cut of 0.05-0.1 mm. The damping hole is machined using a combination of drilling and reaming, with the hole diameter tolerance controlled within ±0.01 mm and the hole position deviation not exceeding 0.01 mm. After machining, the piston surface is precision ground, with a surface roughness controlled within Ra0.04-0.08 μm. Step F, Surface strengthening treatment: The finished piston is subjected to steam treatment at a temperature of 180-220℃ for 20-30 minutes to form a protective oxide layer with a thickness of 5-15μm on the piston surface, so that the surface hardness reaches 180-250HV and the coefficient of friction is reduced to 0.15-0.

25. Step G, Precision Inspection: A combination of fully automated optical inspection equipment and magnetic induction inspection is used to comprehensively inspect the piston's dimensional accuracy, surface quality, hardness, and density. Dimensional inspection covers key indicators such as outer diameter, piston bore diameter, damping hole position, and annular groove width, with an accuracy of ±0.001mm. Surface quality inspection checks for scratches, dents, oxide layer defects, etc. Hardness testing uses a Vickers hardness tester, and density testing uses the water displacement method. Products that fail inspection are reworked or scrapped. Step H, Finished Product Packaging: Clean and dry the qualified pistons at a temperature of 60-80℃ for 30-40 minutes. After drying, wrap them individually with rust-proof paper, then put them into shockproof packaging boxes, label them, and put them into storage.

2. The precision machining process for an automotive shock absorber piston according to claim 1, characterized in that, In step A, the iron-copper alloy powder has a uniform microstructure, a flowability of 15-20 s / 50 g, and a loose packing density of 3.5-4.2 g / cm³.

3. The precision machining process for an automotive shock absorber piston according to claim 1, characterized in that, In step B, the lubricant is zinc stearate with a purity ≥99% and a particle size of 200-250 mesh.

4. The precision machining process for an automotive shock absorber piston according to claim 1, characterized in that, In step C, the protective atmosphere sintering in the sintering furnace is controlled at 0.001-0.01 MPa. During the sintering process, the temperature and atmosphere concentration are monitored in real time, and the temperature fluctuation does not exceed ±5℃.

5. The precision machining process for an automotive shock absorber piston according to claim 1, characterized in that, In step E, the tip radius of the diamond tool is 0.1-0.2 mm, and cutting fluid is used for cooling during the machining process. The cutting fluid is an emulsion, and the cooling temperature is controlled at 20-25℃.

6. The precision machining process for an automotive shock absorber piston according to claim 1, characterized in that, In step G, the inspection adopts a precision tolerance standard, and the minimum tolerance after dimensional adjustment is controlled within ±0.01mm, with an inspection pass rate ≥99.5%.

7. The precision machining process for an automotive shock absorber piston according to claim 1, characterized in that, In step H, ultrasonic cleaning is used, the cleaning solution is a neutral cleaning agent, and the cleaning time is 10-15 minutes. After cleaning, the piston surface is free of oil and impurities.